Presidential Address: Historians in the Present - High, Steven (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
Steven High’s presidential address, delivered at York University in May 2023, grapples with many of the issues facing our discipline and what it means to be a historian in the present. Despite the extreme political polarization of our time, he expressed admiration at the courage of so many historians who continue to speak truth to power, even at considerable risk to themselves. He also addresses the structural violence of precarity within our discipline and what we as a professional association can do about it.